Production of high strength bioliquid from municipal solid waste (MSW) using mixed culture - N., Zainol; Sidek, N. S. M.; Ya’acob, A. (IOP Publishing, 2021)
Landfilling is one of the most commonly used methods of municipal solid waste (MSW) disposal. It is necessary because there are residues in all waste management processes that cannot be reused or recovered further and are essentially landfilled. For the degradation of MSW, thermal, mechanical and biological pretreatment techniques are used. MSW could be treated and converted into liquid biomass (bioliquid) by using enzymes. This research focused on the production of high strength bioliquid in MSW. The experiments were conducted in three stages namely: acclimatization process, preliminary study and factorial analysis to determine the production of high strength bioliquid in MSW. The selected factors were ratio of AMC and substrates (1:2 and 1:5), temperature (room temperature and 37 °C), pH (adjusted pH and no pH adjustment), PET plastics size (1cm2 and 4cm2) and Hydraulic Retention Time (3 hours and 9 hours). Design Expert software (Version 7) was used to construct an experimental table where all the factors were randomized. Two-level factorial analysis (TLFA) was used to analyze the most contributing factor and interaction between the factors. The results showed that the most significant factor was temperature, while the interaction factors were between temperature and HRT. The best conditions of COD increment were determined at AMC/S ratio 1:5, adjusted pH, PET plastics size of 1cm x 1cm, at room temperature and HRT of 3 hours. The experimental and targeted final increments of COD were 2.19 and 1.99 respectively. Since the error was less than 10%, it is acceptable, and the objectives of this research were successfully achieved.